Comprehensive Physiology 2012
DOI: 10.1002/cphy.c110041
|View full text |Cite
|
Sign up to set email alerts
|

Pathophysiology of Acute Kidney Injury

Abstract: Acute kidney injury (AKI) is the leading cause of nephrology consultation and is associated with high mortality rates. The primary causes of AKI include ischemia, hypoxia or nephrotoxicity. An underlying feature is a rapid decline in GFR usually associated with decreases in renal blood flow. Inflammation represents an important additional component of AKI leading to the extension phase of injury, which may be associated with insensitivity to vasodilator therapy. It is suggested that targeting the extension pha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

28
963
0
30

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 976 publications
(1,021 citation statements)
references
References 616 publications
(501 reference statements)
28
963
0
30
Order By: Relevance
“…Additionally, patients with both anemia and AKI had a higher mortality risk than the counterpart groups. This may be because both anemia and AKI aggravate organ dysfunction or delay of organ recovery (Cilley et al 1991;Basile et al 2012). Anemia can have both direct and indirect effects on mortality; in the context of indirect effect, anemia may increase the severity of AKI and worsen the mortality rate.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, patients with both anemia and AKI had a higher mortality risk than the counterpart groups. This may be because both anemia and AKI aggravate organ dysfunction or delay of organ recovery (Cilley et al 1991;Basile et al 2012). Anemia can have both direct and indirect effects on mortality; in the context of indirect effect, anemia may increase the severity of AKI and worsen the mortality rate.…”
Section: Discussionmentioning
confidence: 99%
“…We speculate that the duration of the treatment was also insufficient to trigger hypertension in these animals, considering that another study showed a robust increase in systolic blood pressure with animals exposed to cafeteria diet for 10 weeks 29 . The most important function of the kidney is filtration and excretion of nitrogenous compounds from blood 30 . Creatinine is a good parameter for assessing renal function, since its production only depends on the muscle cell metabolism and is almost entirely eliminated by glomerular filtration [30][31][32] , and by poor tubular secretion 33 , that may be considered insignificant.…”
Section: Discussionmentioning
confidence: 99%
“…The most important function of the kidney is filtration and excretion of nitrogenous compounds from blood 30 . Creatinine is a good parameter for assessing renal function, since its production only depends on the muscle cell metabolism and is almost entirely eliminated by glomerular filtration [30][31][32] , and by poor tubular secretion 33 , that may be considered insignificant. Therefore, the intensity of creatinine excretion corresponds to the rate of glomerular filtration, so if glomerular filtration decreases, its excretion also decreases transiently, increasing its levels in body fluids and plasma until the creatinine excretion returns to normal 34 .…”
Section: Discussionmentioning
confidence: 99%
“…Tubular injury has a link with reduction of RPF through increasing renal vascular resistance, consequently increasing serum creatinine concentration (Fig. 2) [8,9]. Congestive heart failure (CHF) itself can be a cause of proteinuria.…”
Section: Discussionmentioning
confidence: 99%